Guidelines for Promoting Food Tourism in Thailand for Malaysian Tourists Using the 8 P’s Marketing Mix - Detmit, Bongkot; Wongmontha, Seri; Na Thalang, Chawalee (Business Administration and Management Journal Review, 2025)
This study aims to find ways to promote food tourism in Thailand for Malaysian tourists using the 8 P’s marketing mix. Data was collected by using a questionnaire from a sample of 400 Malaysian tourists who had visited Thailand and had eaten Thai foods. The study found that more than 50% of the tourists were male. Age between 31 - 40 years. Occupation is a private company employee. Average monthly income between 4,001 – 6,000 Ringgit. Bachelor’s degree level. Have been to Thailand more than 5 times, traveling with friends/girl & boyfriend. It was found that overall, Tourism has opinions about the 8 P’s marketing mix as a high level. And overall, the demographic characteristics of Malaysian tourists are different. It will affect the 8 P’s marketing mix in promoting food tourism in Thailand that is significantly different at the 0.05 level, Thus, the hypothesis is accepted.